EFFECT OF METHODS AND DURATIONS OF DRYING ON IN VITRO DIGESTION OF GLIRICIDIA MACULATA - Kustantinah, Kustantinah (Universitas Gadjah Mada, 2007)
Research was conducted to evaluate methods and durations of drying of Gliricidia leaves on in vitro digestion. The methods of drying had been direct (DD=under sunshine) or indirect (ID+under shading) and the durations of drying were 0 (fresh) or 6 days. SAmples were prepared by grinding analysis of in vitro digestion to measure fraction readily fermented (a) and total gas production (a+b). Results indicated that duration of drying effected (P<0.05) fraction readily fermented (a) between fresh and 6 days direct drying being 19.01 ml/200 mgBK and 5.57 ml/200 mlBK, while for indirect drying, being 105.63 ml/200 mgBK and 49.36 ml/200 mgBK, respectively. The total gas production indicated that method of drying decreases (P<0.05) value of (a+b) from 124.63 ml/200 mlBK for DD, and from 95.14 ml/200 mgBK to 89.75 ml/200 mgBK for ID. It is concluded that Gliricidia leaves could be stored after drying without affecting utilization of the feed in the rumen.